Pengaruh Strategi Pemasaran Spiritual, Emosional dan Rasional Terhadap Loyalitas Pelanggan Kangen Water di Malang Raya - Wiyodiningrum Eka Nurazizah; Budi Wahono; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to test and explain the effect of spiritual, emotional and rational marketing strategies on kangen water customer loyalty in Malang. The number of samples collected was 100 respondents. By using the Purposive Sampling method as a sampling technique. This study uses multiple linear analysis, using SPSS. The results of this study indicate that spiritual marketing has a significant effect on customer loyalty, emotional marketing has a significant effect on customer loyalty, rational marketing has a significant effect on customer loyalty. Keywords: Spiritual Marketing, Emotional Marketing, Rational Marketing, Customer Loyalty.